Epidemiology of injuries in track and field athletes: a cross-sectional study of specific injuries based on time loss and reduction in sporting level - Lambert, C.; Reinert, N.; Stahl, L.; Pfeiffer, T.; Wolfarth, B.; Lachmann, D.; Shafizadeh, S.; Ritzmann, R. (The Physician and Sportsmedicine, 2022)
Objectives To prevent the occurrence of injury in a sport, exact knowledge of injury patterns is needed. To synthesize sport-specific injuries in track and field comparing elite and recreational level athletes, as well as gender. Furthermore, analyze the time loss due to injury and reduction in athletic performance.